ANTICONVULSANT PROPERTIES OF SOME MEDICINAL PLANTS- A REVIEW - Srinivasan, Nivedha; Roy, Anitha (Asian Journal of Pharmaceutical and Clinical Research, 2017)
Introduction: Epilepsy is the tendency to have seizures that start in the brain. The brain uses electrical signals to pass messages between brain cells and when these signals are disrupted, it leads to a seizure. A number of synthetic antiepileptic drugs are available in practice, but various medicinal plants act as an important source of treatment for epilepsy; plants such as Aeollanthus suaveolens, Passiflora caerulea, Persea americana, Annona diversifolia, and Boerhavia diffusa have good anticonvulsant activity. Objective: Anticonvulsant drugs are used to control the convulsions by inhibiting the discharge and then producing hypnosis. The objective is to understand various medicinal plants and plant components, which are being used as an anticonvulsant. Results: A. suaveolens essential oils are the main constituents were deemed to display anticonvulsant activity. P. caerulea is reputed to have herbal activity as a sedative and anticonvulsant and it is often used as a relatively disease resistant root stock. Whereas P. americana, extract produces its anticonvulsant effect by enhancing gamma-aminobutyric acid ergic neurotransmission and or action in the brain. B. diffusa consists of a calcium channel antagonist compound, liriodendrin that is responsible for its anticonvulsant activity. Conclusion: Since epilepsy has become a common brain disorder, having knowledge of the medicinal plants with an anticonvulsant activity will be beneficial to the society. Keywords: Antiepileptic, Aeollanthus suaveolens, Passiflora caerulea, Persea americana, Annona diversifolia, Boerhavia diffusa.